ANALISIS REGULASI PENGEMBANGAN PRODUK UNGGULAN SUMATERA UTARA BERBASIS DESA - Afri Winata Lubis; Lailan Tawwila; Syafri Syafri; Jonni Sitorus (Jurnal Agriuma, 2021)
In North Sumatra, rural areas are areas that dominate extraordinary potential, such as agriculture, tourism, culinary and various community handicrafts. If it is managed and developed optimally, it can accelerate development in North Sumatra. The focus of developing the village and managing the city has been prepared through concrete steps that must be taken by the North Sumatra Provincial Government, while the development of leading industries in North Sumatra Province focuses on superior products per Regency/City. However, unfortunately the village or local government officials have not been maximal in following up on superior product programs. As for the purpose of this research, the purpose of research on regulations for the development of superior regional products is to be aligned with the objectives of developing superior product-based industries in North Sumatra Province by still referring to the regulations set by the minister of home affairs, namely (1). Increase the growth of the village-based leading product industry sector in North Sumatra, (2) Increase the export value of industrial products without oil and gas, (3). Increasing the value of investment in the industrial sector without oil and gas, (4) Increasing production and value-added regional potential. The method used in this study was a participatory approach through interviews to analyze local government understanding of how village-based regional superior product regulations or regulations can be useful in accordance with the goals and objectives of their preparation. The results of the research show that the regulations regarding the development of superior products of North Sumatra still refer to the Regulation of the Minister of Home Affairs of the Republic of Indonesia and also the understanding of the local government according to the statement indicators given and there is still no coordination between ORGANISASIÂ